1997
DOI: 10.1021/jf970362z
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Adsorption of Fipronil on Soils

Abstract: A comparative study of the adsorption of fipronil, a phenylpyrazole acridicide, on two Sahelian soils (Saguia and Banizoumbou in Niger) and a Mediterranean soil (Montpellier) has shown that this phenomenon is dependent on the level of organic matter (OM):  the adsorption coefficients (K f) were, respectively, 4.3 (Saguia, 0.1% OM), 7.3 (Banizoumbou, 0.3% OM), and 45.5 (Montpellier, 6.5% OM). The partial destruction of the OM of the Montpellier soil sample by oxidation with hydrogen peroxide confirmed the funda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
67
0
12

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(82 citation statements)
references
References 20 publications
3
67
0
12
Order By: Relevance
“…The result is that over a certain range of concentration, more Þpronil molecules will be present in the aqueous phase. In the case of Þpronil it was also demonstrated that there was a signiÞcant decrease in adsorption coefÞcient as the soil organic matter and clay content decreased (Bobe et al 1997). This explains more bioavailability of the Þpronil in soils with lower organic matter because of the small amount of organic phase available for Þpronil molecules.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…The result is that over a certain range of concentration, more Þpronil molecules will be present in the aqueous phase. In the case of Þpronil it was also demonstrated that there was a signiÞcant decrease in adsorption coefÞcient as the soil organic matter and clay content decreased (Bobe et al 1997). This explains more bioavailability of the Þpronil in soils with lower organic matter because of the small amount of organic phase available for Þpronil molecules.…”
Section: Discussionmentioning
confidence: 88%
“…Few data are available on the degradation of Þpronil (Bobe et al 1997) and even less so for the rates applied as termiticides. When applied at Þeld application rates (8 g [AI]/ha), 75% of the Þpronil degraded within 3 d, and the four metabolites were detected (Bobe et al 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6) The parent insecticide and its degradation products each possesses unique dissipation kinetics which are presented below.…”
Section: Environmental Degradationmentioning
confidence: 99%